A novel anti islanding detection method for grid connected fuel cell power generation systems - Bayrak, Gokay; Cebeci, Mehmet (Pergamon-Elsevier Science Ltd, 2014)
Renewable energy sources have been developed rapidly all around the world, and one of these green energy sources is hydrogen energy. The fuel cell systems have become prominent in renewable energy sources because of its minimal dimensions and energy conversion method. There have been developed, some applications, especially in domestic and automotive areas, and fuel cell systems are also have been started to use in grid connected systems. Fuel cell systems must have some electrical connection standards while they connected to an electrical grid. One of these electrical conditions and may be the most important one is unplanned islanding condition. Islanding is a very dangerous situation because it can damage to the fuel cell and related electrical systems and also working people have been at risk in islanding situation on the grid. In this study, a novel islanding detection method was introduced for grid connected fuel cell systems. 0.5 kW solid oxide fuel cell (SOFC) system used in developed experimental system and a novel anti islanding detection method was researched by using an effective method. The proposed method was also developed by using Matlab Simulink and its useful tools. The developed islanding detection method is robust, reliable and has a fast response time, according to present methods. The results confirm the suggested conditions, and it can be seen in this method, it can also be adapted easily to the grid connected fuel cell systems. Copyright (C) 2014, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Fuel cell power generation system; SOFC; Islanding; Islanding detection; Data acquisition